Perbandingan Akurasi Metode Dempster-Shafer dan Certainty Factor pada Sistem Pakar Penyakit Zoonosis - Teguh Ansyor Lorosae; Sahrul Ramadhan; K Khairunnisa (LPPM STIKOM Tunas Bangsa, 2023)
In Indonesia there are still health problems where infectious diseases are increasing, more than 60% of disease cases in the world are zoonotic diseases and about 70% of zoonotic diseases come from animals. In Indonesia, there are 132 species of micro-organisms that are zoonotic. The Minister of Health also warned in recent years about emerging and re-emerging zoonotic diseases, 'emerging zoonoses' are zoonotic diseases that have just emerged, can occur anywhere in the world, and the impact is potentially severe such as, losses at the time of the outbreak, the cost of disease management, post-outbreak losses, quarantine costs, losses due to the restoration of public awareness and the fear of consuming livestock products. This study will compare the accuracy of the Dempster-Shafer and Certainty Factor methods in zoonotic disease expert systems. Based on the results of Confusion Matrix theory testing, 99% accuracy of the Dempster-Shafer method and 100% accuracy of the Certainty Factor method were obtained.